Antithrombotic Treatment After Coronary Intervention: Agreement and Controversy - Tamara García Camarero (Radcliffe Medical Media, 2020)
Percutaneous revascularisation has evolved dramatically in the past few decades. The approach to the management of ischaemic heart disease has changed due to the development of new devices and techniques as well as the availability of new drugs and treatment strategies. Its use in combination with antiplatelet therapies has been essential to protect against stent thrombosis. The length of time this combination therapy is used has been modified in recent years and has been the subject of extensive research. The effect of prolonging the time it is taken or shortening it has been evaluated in different clinical conditions. In practice, the decisions regarding antithrombotic therapy after percutaneous coronary intervention are informed by the patient’s profile and the characteristics of the procedures performed. In this article, we review the use of antiplatelet/anticoagulant therapy after percutaneous coronary intervention focusing on trials and guidelines addressing variable durations for combination regimens and the alternatives.